Klasifikasi Citra Ras Kucing Berbasis CNN dengan Metode MobileNet-V2 - Hermawan, Ramadhan Anugrah; Taufik, Ichsan; Aditia Gerhana, Yana (Masoem University, 2025)
This study evaluates the performance of a Convolutional Neural Network (CNN) using the MobileNet-V2 architecture in classifying four cat breeds. The lack of public understanding in distinguishing cat breeds, especially due to the prevalence of mixed breeds, presents a significant challenge in accurate identification. The model was tested across multiple epochs to observe training and validation accuracy, aiming to assess its effectiveness and stability. Experimental results show that the highest validation accuracy of 93.81% was achieved at epoch 90. Although the model performed well, further optimization is needed to address overfitting and improve generalization capability. This research contributes to the development of an automated breed identification system that can be applied in education, adoption processes, and veterinary healthcare.